An Extended Book Review: History Is Not Optional: A Response to THE REAL JESUS by Luke Timothy Johnson - Miller, Robert J. (Biblical theology bulletin, 1998)
THE REAL JESUS: THE MISGUIDED QUEST FOR THE HISTORICAL JESUS AND THE TRUTH OF THE TRADITIONAL GOSPELS, by Luke Timothy Johnson (San Francisco, CA: HarperCollins, 1996; vi + 182 pp.; paper, $12.00) presents itself as a reasoned refutation of recent historical Jesus research. In reality it is a deeply flawed and extremist defense of Christian orthodoxy. This essay analyzes four aspects of Johnson's argument. The harshness of Johnson's polemics creates the impression of a powerful critique, but serves mainly to distract the reader from the lack of substance in his arguments. Johnson's specific criticisms of recent historical Jesus books are very weak and appeal primarily to readers' emotions. Johnson believes that the search for the historical Jesus is misguided because, in his view, the Gospels are virtually worthless historically. This is an extremist position rejected by the vast majority of biblical scholars. Johnson's position that early Christianity can be explained only by a miracle (the resurrection) is transparently apologetic. Johnson attempts to protect the traditional theological picture of Christian origins by declaring it off-limits to historical-critical inquiry.